Who Knows, who Cares? Dementia Knowledge among Nurses, Care Workers, and Family members of People Living with Dementia. Issue 3 (September 2014) - Robinson, Andrew; Eccleston, Claire; Annear, Michael; Elliott, Kate-Ellen; Andrews, Sharon; Stirling, Christine; Ashby, Michael; Donohue, Catherine; Banks, Susan; Toye, Christine; McInerney, Fran
The number of people with dementia is increasing rapidly worldwide. Commensurate with population ageing, the use of nursing homes in Australia (known as residential aged care facilities) for individuals with dementia is growing. As a terminal condition, dementia is best managed by instituting a palliative approach to care. A good knowledge of dementia, including its progression and management, among staff and families of people living with dementia is essential for clear decision making and the provision of appropriate care. Yet there is limited information regarding relative levels of dementia knowledge. This paper reports the results of a study that assessed dementia knowledge among these two cohorts using the Dementia Knowledge Assessment Tool; the study surveyed 279 staff members and 164 family members of residents with dementia. Dementia knowledge deficits were evident in both cohorts across a range of areas. It is critical that dementia knowledge deficits are identified and addressed in order to support evidence-based dementia care. Le nombre de personnes atteintes de démence augmente rapidement à travers le monde. Ainsi on remarque en Australie une augmentation du nombre de ces malades admis dans les institutions de soins de longue durée. La démence étant une maladie terminale il appert que l'approche palliative est la meilleure forme de soins. Cependant, il est essentiel que le personnel soignant autant que les familles aient une bonne connaissance de la maladie, de ses symptomes, de la façon de traiter les maladies, et des décisions à prendre. Or, on en sait très peu quant au niveau de connaissances de ces deux groupes de personnes sur le sujet. Cet article porte sur les résultats d'une étude qui tentait d'évaluer le niveau de connaissances de 279 membres du personnel et de 164 membres des familles à l'aide de l'Έchelle d'évaluation des connaissances sur la démence. Le peu de connaissances était évident chez les deux cohortes et ce, sur un bon nombre de points. Il est donc de la plus haute importance que l'on identifie spécifiquement ces points et qu'on améliore la qualité des soins chez les personnes démentes en se basant sur des données probantes.